2022
DOI: 10.24259/fs.v6i1.19160
|View full text |Cite
|
Sign up to set email alerts
|

Between Hopes and Threats: New Migratory Birds Records on the Sawala Mandapa Education and Training Forest, Indonesia

Abstract: Java Island is one of the tropical areas for bird migration, especially the Asian-Australian flyway of migratory birds. The SMETF is one of the protected forest areas that migratory birds can visit in Java. This research aims to identify migratory birds in SMETF. Transect and point count methods are used to observe migratory bird movements and their activities. In the research area, four migratory birds were identified: Ficedula zanthopygia, Agropsar sturninus, Pernis ptilorhynchus o., and Accipiter soloensis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Lanius cristatus, Lanius tigrinus, and Ficedula zanthopygia are migratory birds from the songbird (Eaton et al 2021;MacKinnon et al 2010). Accipiter soloensis, Accipiter badius, and Pernis ptilorhyncus are migratory birds from the raptor (Germi 2005;Germi et al 2013;Iswandaru et al 2022;Nijman 2001Nijman , 2005Nijman et al 2006). Glareola maldivarum is a migratory bird from the waterbird (Gönner et al 2014;Susanto et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lanius cristatus, Lanius tigrinus, and Ficedula zanthopygia are migratory birds from the songbird (Eaton et al 2021;MacKinnon et al 2010). Accipiter soloensis, Accipiter badius, and Pernis ptilorhyncus are migratory birds from the raptor (Germi 2005;Germi et al 2013;Iswandaru et al 2022;Nijman 2001Nijman , 2005Nijman et al 2006). Glareola maldivarum is a migratory bird from the waterbird (Gönner et al 2014;Susanto et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these migratory birds is a unique attraction because they can only be found in the buffer village between October-April when their breeding habitat experiences winter. They migrate to the tropics for a warm environment and abundant food sources because it is available all year round (Iswandaru et al 2022;Sodhi et al 2011). This result indicated that the buffer villages around WKNP have the potential as wintering habitats or stopover areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Birds are wild animals that use the peat ecosystem as a place to live and find food (Pramudianto 2018). Ecologically, birds have an important role in dispersing seeds (Ning et al 2019) and helping flower pollination (Lindell and Thurston, 2013;Iswandaru et al 2022) and have a high sensitivity to climate change (Li et al 2021). Birds are one of the animals with the top position in the food chain, making them sensitive to prey and environmental changes (Egwumah et al 2017).…”
Section: Introductionmentioning
confidence: 99%